Cyganie vs Romowie w Hiszpanii. Przynależność etniczna, język i tożsamość - Biernacka, Maja (Człowiek i Społeczeństwo, 2017)
The paper scrutinizes the particularities of the terms Gypsy and Romaní and selected differences between them in the context of the Spanish society. The first notion refers to the ethnicity which has been historically linked with the Iberian Peninsula since the first half of the fifteenth century and the term Romaní is used with reference to nomadic groups mainly from the Balkans. While the notion ‘Gypsy’ has been abandoned in Central and Eastern Europe as disparaging, its equivalent i.e. gitano is legitimate and acceptable in Spain. The article also draws upon some of qualitative research carried out by the author in Spain, i.e. participant observation and unstructured interviews conducted with the Gypsies with a focus on identity and language issues.